Embedded DRAM technology opportunities and challenges. - Iyer, S.S (IEEE spectrum)
Embedding dynamic RAMs will give system designers large amounts of high-bandwidth, high-performance memory to apply to completely new functions. Although embedding DRAM allows for a new dimension in large-scale integration, the path to success is not smooth. Redesigning at the system level is a must for exploiting the wide memory widths to obtain the performance available-merely mapping existing designs results in larger chips with lower yields in more expensive technologies. The creative designer, who innovates and redesigns, will be the winner in the new world of embedded DRAM